Flexible electricity use for heating in markets with renewable energy - Wolf-Peter Schill; Alexander Zerrahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Using electricity for heating can contribute to decarbonization and provide flexibility to integrate variable renewable energy. We analyze the case of electric storage heaters in German 2030 scenarios with an open-source electricity sector model. Making customary night-time storage heaters temporally more flexible offers only moderate benefits because renewable availability during daytime is limited in the heating season. As storage heaters feature only short-term heat storage, they also cannot reconcile the seasonal mismatch of heat demand in winter and high renewable availability in summer. Generally, flexible electric heaters increase the use of generation technologies with low variable costs, which are not necessarily renewables.
Keywords: C61; Q41; Q42; 330; power-to-heat; renewable energy; electricity sector; power system model; flexibility; storage